Tatar first names from West Siberia: an English and Russian dictionary : with native-speaker pronunciation CD - Louson E. D. Edvin D.; Zaviyalova Z. S. Zinaida Sergeevna; Sheil R. F. Richard F. (San Diego, HtComGroup, [2014])
This dictionary includes more than 500 names with explanations of their meaning and a pronunciation guide with elaborated analytical material including linguistic, statistical and sociological analysis. All renderings of names in the International Phonetic Alphabet are missing from this edition. Accompanying DVD contains a slideshow presenting many of the findings of the book, with screen captures and accompanying sound for each dictionary entry.